(untitled) (Research, Society and Development, 2022)
Introduction: diabetes mellitus is characterized by being a problem of great global disorder, with the capacity for acute and chronic morbidities. One of the main disorders is ulcerative lesions in the extremities, as in the feet, and when there is a bad evolution of the patient’s condition, it can result in amputation of the affected limb. Ozone therapy is an alternative treatment option for these types of injuries due to its performance in oxidative stress, which results in a good recovery of the individual, with subsequent angiogenesis and wound healing, and can be used in addition to conventional treatment, since has antimicrobial action. Objective: To verify from the available literature what is the influence of ozone therapy as an adjuvant in the treatment of ulcerous wounds of diabetic foot. Methods: Integrative literature review based on the descriptors "Ozone", "Complementary Therapies", "Diabetic Foot" and "Diabetes Mellitus", using the PubMed and BSV database, resulting in 17 articles for complete analysis and selecting 11 with greater relevance. Results: Ozone therapy can be used as an adjunctive treatment in the treatment of diabetic foot ulcers, as concluded in 8 (72.7%) studies analyzed, but 3 (27.2%) concluded that there were not enough studies for an outcome on the subject, in addition to warning that adjuvant therapies are only used when conventional treatments are not effective. Despite the positive evidence observed in relation to the use of ozone as an adjuvant in the treatment of diabetic foot ulcers, in Brazil, the Federal Council of Medicine (CFM) establishes ozone therapy only as an experimental procedure. Conclusion: Most articles analyzed in this literature review indicate that ozone therapy is efficient in the treatment of ulcerated lesions in diabetic patients, however the number of studies carried out in these areas is still reduced, making a larger and more diverse range of studies necessary studies referring to this alternative practice.